Pengaruh Profitabilitas, Lagged Dividend, Size, dan Leverage pada Kebijakan Dividen - Selaristi Izdihar; Suhendro Suhendro; Rosa Nikmatul Fajri (Jurnal Ilmiah Universitas Batanghari Jambi, 2020)
This study aims to examine and analyze the effect of profitability, lagged dividends, size, and leverage on dividend policy. The population in this study are companies in the consumer goods industry sector which are listed on the Indonesia Stock Exchange (BEI) in 2016-2018. This type of research is quantitative research. Sampling with purposive sampling technique resulted in 19 companies in the consumer goods industry sector in 2016-2018 according to the specified criteria, in order to obtain 57 research data. This study uses multiple linear regression analysis with the SPSS version 23. IMB program. The results of this study concluded that profitability and lagged dividends affect the dividend policy. While size and leverage have no effect on dividend policy.